2008
DOI: 10.1007/s10067-008-1016-8
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing polychondritis—case series from South India

Abstract: Relapsing polychondritis (RP) is a rare recurring inflammatory disorder with variable clinical course. It has been described mainly in Caucasian population. Reports from other ethnic groups are few. We report seven cases of relapsing polychondritis in south Indian population. In between 1995 and 2008, seven patients fulfilling the McAdam-Damiani-Levine criteria for diagnosis of relapsing polychondritis were identified. Records pertaining to these patients were studied and clinical presentation, course, and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 12 publications
0
18
1
Order By: Relevance
“…In a case series conducted in an Oriental population [7], it was observed that the disease course was similar to that in the Caucasian population except that cutaneous, renal or nervous system involvement was not seen and the incidence of airway complications was more. Another series from North India [8] reported that the clinical features were similar, but laryngotracheal involvement was less frequent in these patients, whereas that from Southern India [9] inferred that auricular and skin involvement were less common.…”
Section: Epidemiologymentioning
confidence: 97%
“…In a case series conducted in an Oriental population [7], it was observed that the disease course was similar to that in the Caucasian population except that cutaneous, renal or nervous system involvement was not seen and the incidence of airway complications was more. Another series from North India [8] reported that the clinical features were similar, but laryngotracheal involvement was less frequent in these patients, whereas that from Southern India [9] inferred that auricular and skin involvement were less common.…”
Section: Epidemiologymentioning
confidence: 97%
“…Case series from western nations defined its clinical spectrum [1-3]. Smaller series from south-east Asia and India have, however, depicted clinical presentations at variance from those in Caucasian patients [4-6] (see Table 1). To document these differences, we present the largest single centre experience from the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Some authors report no significant gender predilection, 1,3,4,11,12 while others find a female preponderance with a female-to-male ratio of 2:1 to 3:1. 1,13,14 The peak age of onset is the fourth or fifth decade of life; 1,4,8,14,15 two large studies describe patients ranging between the age of 3 to 87 years. 8,16 …”
Section: Epidemiologymentioning
confidence: 99%